Co(II) and Cd(II) Complexes Derived from Heterocyclic Schiff-Bases: Synthesis, Structural Characterisation, and Biological Activity - Riyadh M. Ahmed; Enaam I. Yousif; Mohamad J. Al-Jeboori (The Scientific World Journal)
New monomeric cobalt and cadmium complexes with Schiff-bases, namely, N′-[(E)-(3-hydroxy-4-methoxyphenyl)methylidene]furan-2-carbohydrazide (L1) and N′-[(E)-(3-hydroxy-4-methoxyphenyl)methylidene]thiophene-2-carbohydrazide (L2) are reported. Schiff-base ligands L1 and L2 were derived from condensation of 3-hydroxy-4-methoxybenzaldehyde (iso-vanillin) with furan-2-carboxylic acid hydrazide and thiophene-2-carboxylic acid hydrazide, respectively. Complexes of the general formula [M(L)2]Cl2 (where M = Co(II) or Cd(II), L = L1 or L2) have been obtained from the reaction of the corresponding metal chloride with the ligands. The ligands and their metal complexes were characterised by spectroscopic methods (FTIR, UV-Vis, 1H, and 13C NMR spectra), elemental analysis, metal content, magnetic measurement, and conductance. These studies revealed the formation of four-coordinate complexes in which the geometry about metal ion is tetrahedral. Biological activity of the ligands and their metal complexes against gram positive bacterial strain Bacillus (G+) and gram negative bacteria Pseudomonas (G−) revealed that the metal complexes become less resistive to the microbial activities as compared to the free ligands.